A proton conductor and its preparation method and application
By using proton conductors composed of niobium iodolate HNbO(IO3)4, boron phosphate BPO4 and inorganic oxide MO2, the problem of degradation of existing fuel cells under medium and high temperature conditions is solved, and the effect of high proton conductivity and high temperature resistance is achieved, reducing costs and simplifying the hydrothermal management system.
Patent Information
- Application Number
- CN202211401009.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-09
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2042-11-09
AI Technical Summary
The existing proton exchange membrane fuel cells have problems such as low environmental adaptability, low utilization efficiency of precious metal catalysts, high cost and complex hydrothermal management systems, especially in the mid-to-high temperature conditions, which are difficult to maintain efficient performance.
The proton conductor consisting of niobium oxyniobium iodoate HNbO(IO3)4, boron phosphate BPO4 and inorganic oxide MO2 is used to synthesize through complexation reaction and self-assembly technology, and BPO4 is introduced in combination with ball milling to form a composite material with high proton conductivity.
The resulting proton conductor has high proton conductivity in the range of 100 to 300°C, good chemical stability, and high temperature resistance. It can effectively improve the performance of fuel cells, reduce the use of precious metal catalysts, and simplify the hydrothermal management system.
Smart Images

Figure HDA0003934977350000011
Abstract
Description
Technical Field
[0001] The invention relates to a proton conductor and a preparation method and application thereof, belonging to the fields of new material technology and new energy technology. Background Art
[0002] Proton exchange membrane fuel cells with proton exchange membrane as electrolyte have the characteristics of high energy conversion efficiency, low operating temperature, fast start-up and long life. They can be widely used as power sources for vehicles and fixed power stations. They are the fuel cells with the most promising commercial applications. At present, proton exchange membrane fuel cells have problems such as low environmental adaptability, low utilization efficiency of precious metal catalysts, high cost and complex water thermal management system. It is generally believed that increasing the operating temperature of fuel cells is an effective countermeasure to solve these problems. When the operating temperature of proton exchange membrane fuel cells is increased above 100℃, the battery reaction kinetics will increase, the catalytic efficiency of Pt catalyst will increase, and the amount of Pt catalyst used can be greatly reduced; and the tolerance of Pt catalyst to CO also increases exponentially with temperature; at the same time, increasing the operating temperature will reduce the battery's requirements for water thermal management system. However, too high temperature (above 500℃) will place more stringent requirements on the component materials of proton exchange membrane fuel cells. Therefore, it is of great significance to develop medium and high temperature (100-500℃) proton exchange membrane fuel cells.
[0003] In view of the unique advantages of medium and high temperature proton exchange membrane fuel cells, the research on medium and high temperature fuel cells has become a research hotspot. As the core component of proton exchange membrane fuel cells, the proton exchange membrane plays the role of isolating fuel and oxidant and conducting protons. Its performance is directly related to the performance of the entire fuel cell. The proton conductor plays the role of proton conduction in the proton exchange membrane. Therefore, the research on high temperature resistant proton conductors is currently a top priority. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a proton conductor and a preparation method and application thereof.
[0005] The present invention provides a proton conductor, comprising niobium iodate HNbO (IO 3 ) 4 , Boron Phosphate BPO 4 and inorganic oxides MO 2 First, niobium pentoxide, hydrofluoric acid, ammonia water and iodic acid are used as raw materials to synthesize iodine niobium oxide HNbO (IO 3 ) 4 Then, under the action of surfactant, iodine niobium oxide HNbO(IO 3 ) 4 It self-assembles with inorganic oxides into a highly ordered electrolyte structure. Then, BPO is introduced by ball milling.4 , a proton conductor can be obtained. 3 ) 4 In the niobium ion, the iodic acid group and the oxygen anion coordinate to form an overall negatively charged framework, and the hydrogen protons diffuse effectively between the oxygen anion and the terminal oxygen atom of the iodic acid group. Therefore, iodic acid oxygen niobium HNbO (IO 3 ) 4 It has its own hydrogen bond network. It self-assembles with inorganic oxides into a highly ordered electrolyte structure. The inorganic oxide crystal size is at the nanoscale, which can provide abundant surface area, and at the same time, it acts as a carrier and skeleton with iodinated niobium HNbO (IO 3 ) 4 It has strong interactions, can enrich the hydrogen bond network and promote proton conduction. In addition, BPO 4 The introduction of further improves the proton conductivity of the material. The obtained material has good chemical stability, high temperature resistance, and high proton conductivity in the range of 100 to 300°C. The proton conductor prepared by the present invention can be used as a proton conductor in the fields of proton exchange membrane additives, fuel cell membrane electrode proton conduction materials, etc.
[0006] The present invention provides a proton conductor, wherein the proton conductor is composed of niobium iodate HNbO (IO 3 ) 4 , Boron Phosphate BPO 4 and inorganic oxides MO 2 composition.
[0007] Furthermore, the inorganic oxide MO 2 Including SiO 2 、TiO 2 or ZrO 2 One or two of the inorganic oxide MO 2 The crystal size is 100~500nm.
[0008] Furthermore, the iodine niobium oxide HNbO(IO 3 ) 4 With inorganic oxide MO 2 The mass ratio is 1:(2-15).
[0009] Furthermore, the boron phosphate BPO 4 With niobium iodate HNbO(IO 3 ) 4 and inorganic oxides MO 2 The mass ratio of the sum of the two is 1:(2.5-25).
[0010] Furthermore, the proton conductor has good chemical stability, high temperature resistance, and high proton conductivity in the range of 100 to 300° C. The high temperature resistance means that it still has good performance in the range of 100 to 300° C.
[0011] The present invention also provides a method for preparing a proton conductor, comprising the following steps:
[0012] (1) 0.4-0.9 mmol of niobium pentoxide is mixed with 3-8 ml of hydrofluoric acid with a mass fraction of 40%, heated to 100-140° C. to dissolve, ammonia water is added to adjust the pH to 5-7, 5-12 ml of 1 mol / L iodic acid aqueous solution is added, the mixture is sealed, and statically treated at 150-180° C. for 48-72 hours; the obtained product is filtered, washed, dried, and calcined at 400-600° C. for 4-12 hours to obtain iodinated niobium HNbO(IO 3 ) 4 ;
[0013] (2) 1 g of niobium iodate HNbO (IO 3 ) 4 2 to 10 g of water is added, stirred for 30 to 60 minutes, and then an inorganic oxide precursor and a surfactant are added and mixed, and stirring is continued for 30 to 60 minutes, and the mixture is sealed and statically treated at 80 to 140° C. for 6 to 18 hours. The static treatment mentioned in the present application means placing the mixture without any other treatment. The obtained product is filtered, washed, dried, and calcined at 400 to 600° C. for 6 to 18 hours to obtain iodinated niobium HNbO(IO 3 ) 4 and inorganic oxides MO 2 mixture of
[0014] (3) mixing phosphoric acid and boric acid (molar ratio 2:1) solutions, heating to 220-280° C. to obtain a boron phosphate precursor; calcining the boron phosphate precursor at high temperature to obtain BPO 4 ;
[0015] (4) BPO prepared in step (3) 4 Add 0.5 to 2 g of water, mix with the mixture prepared in step (2) by ball milling, and dry to obtain the proton conductor.
[0016] Furthermore, the inorganic oxide precursor includes one or two of tetraethyl orthosilicate, ethyl titanate, butyl titanate, tetraethoxysilane, and ethyl zirconate, the surfactant includes one of F127, P123, and CTAB, and the mass ratio of the inorganic oxide precursor to the surfactant is (5-15):3.
[0017] Furthermore, the temperature of high temperature calcination of the boron phosphate precursor is 300-600° C. and the time is 2-24 hours.
[0018] The present invention also provides the use of the proton conductor in a proton exchange membrane additive or a fuel cell membrane electrode proton conductive material, and the applicable temperature is 100-300°C.
[0019] Compared with the prior art, the proton conductor provided by the present invention has the following advantages: iodinated niobium HNbO (IO 3 ) 4 The nano-scale inorganic oxides have their own hydrogen bond network, which can provide abundant surface area, and can also act as carriers and skeletons, while cooperating with iodinated niobium HNbO(IO 3 ) 4 It has strong interactions, can enrich the hydrogen bond network and promote proton conduction. In addition, BPO 4 The introduction of further improves the proton conductivity of the composite material. The resulting material has good chemical stability, high temperature resistance, and high proton conductivity in the range of 100-300°C. The proton conductor prepared by this patent can be used as a proton conductor in the fields of proton exchange membrane additives, fuel cell membrane electrode proton conduction materials, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a scanning electron microscope image of the proton conductor in Example 1 of the present invention. DETAILED DESCRIPTION
[0021] The present application is described in detail below in conjunction with embodiments, but the present application is not limited to the following embodiments.
[0022] Example 1
[0023] 1) Mix niobium pentoxide (0.6 mmol) and hydrofluoric acid (40% by mass, 4 ml), heat to 120°C and stir until dissolved, add ammonia water to adjust the pH to 6; add 10 ml of 1 mol / L iodic acid aqueous solution, seal, and statically treat at 180°C for 60 hours. The obtained product is filtered, washed, dried, calcined at 500°C for 6 hours, and ground into a uniform powder to obtain iodinated niobium HNbO(IO 3 ) 4 ;
[0024] 2) 1g niobium iodate HNbO(IO 3 ) 4 Add 5g of water, stir for 30 minutes, then add 15g of tetraethyl orthosilicate TEOS and 3g of surfactant P123, continue stirring for 30 minutes, seal, and statically treat at 120°C for 12 hours. The obtained product is filtered, washed, dried, and calcined at 500°C for 18 hours to obtain iodine niobium oxide HNbO (IO3 ) 4 and silicon dioxide SiO 2 mixture of
[0025] 3) Phosphoric acid and boric acid (molar ratio 2:1) were mixed, heated to 260°C and stirred continuously to obtain a white slurry precursor. The obtained precursor was calcined at 350°C in a muffle furnace for 20 hours, and the obtained material was ground into a uniform powder, namely BPO. 4 powder;
[0026] 4) 0.4 g of BPO prepared in step 3) 4 The powder was added to 1 g of water, mixed with 1.0 g of the mixture prepared in step 2) by ball milling for 8 hours, and dried to obtain a proton conductor, which was designated as NbBPSi-1.
[0027] Taking NbBPSi-1 as the proton conductor, the conductivity at 120°C and 10RH% is 0.185S / cm; at 280°C and 5RH%, the conductivity is 0.198S / cm.
[0028] Example 2
[0029] 1) Mix niobium pentoxide (0.6 mmol) and hydrofluoric acid (40% by mass, 4 ml), heat to 100°C and stir until dissolved, add ammonia water to adjust the pH to 6; add 10 ml of 1 mol / L iodic acid aqueous solution, seal, and statically treat at 150°C for 48 hours. The obtained product is filtered, washed, dried, calcined at 400°C for 12 hours, and ground into a uniform powder to obtain iodinated niobium HNbO(IO 3 ) 4 ;
[0030] 2) 1g niobium iodate HNbO(IO 3 ) 4 Add 5g of water, stir for 30 minutes, then add 12g of butyl titanate and 3g of surfactant P123, continue stirring for 30 minutes, seal, and statically treat at 140°C for 8 hours. The obtained product is filtered, washed, dried, and calcined at 550°C for 14 hours to obtain iodine niobium oxide HNbO (IO 3 ) 4 and titanium dioxide TiO 2 mixture of
[0031] 3) Phosphoric acid and boric acid (molar ratio 2:1) were mixed, heated to 220°C and stirred continuously to obtain a white slurry precursor. The obtained precursor was calcined at 350°C in a muffle furnace for 20 hours, and the obtained material was ground into a uniform powder, namely BPO. 4 powder;
[0032] 4) 0.2 g of BPO prepared in step 3) 4 The powder was added to 1 g of water, mixed with 1.0 g of the mixture prepared in step 2) by ball milling for 8 hours, and dried to obtain a proton conductor, which was designated as NbBPTi-1.
[0033] Taking NbBPTi-1 as the proton conductor, the conductivity at 120°C and 10RH% is 0.187S / cm; at 280°C and 5RH%, the conductivity is 0.199S / cm.
[0034] Comparative Example 1
[0035] 1) Mix niobium pentoxide (0.6 mmol) and hydrofluoric acid (40% by mass, 4 ml), heat to 120°C and stir until dissolved, add ammonia water to adjust the pH to 6; add 10 ml of 1 mol / L iodic acid aqueous solution, seal, and statically treat at 180°C for 60 hours. The obtained product is filtered, washed, dried, calcined at 600°C for 4 hours, and ground into a uniform powder to obtain iodinated niobium HNbO(IO 3 ) 4 ;
[0036] 2) Phosphoric acid and boric acid (molar ratio 2:1) were mixed, heated to 220°C and stirred continuously to obtain a white slurry precursor. The obtained precursor was calcined at 350°C in a muffle furnace for 20 hours, and the obtained material was ground into a uniform powder, namely BPO. 4 powder;
[0037] 3) 0.2 g of BPO prepared in step 2) 4 The powder was added to 1 g of water and 1.0 g of iodinated niobium oxide HNbO (IO 3 ) 4 The mixture was mixed by ball milling for 8 hours and dried to obtain a proton conductor, which was designated as NbBP-1.
[0038] Taking NbBP-1 as the proton conductor, the conductivity at 120°C and 10RH% is 0.135S / cm; at 280°C and 5RH%, the conductivity is 0.169S / cm.
[0039] Comparative Example 2
[0040] 1) Mix niobium pentoxide (0.6 mmol) and hydrofluoric acid (40% by mass, 4 ml), heat to 120°C and stir until dissolved, add ammonia water to adjust the pH to 6; add 10 ml of 1 mol / L iodic acid aqueous solution, seal, and statically treat at 180°C for 60 hours. The obtained product is filtered, washed, dried, calcined at 450°C for 12 hours, and ground into a uniform powder to obtain iodinated niobium HNbO(IO 3 )4 ;
[0041] 2) 1g niobium iodate HNbO(IO 3 ) 4 Add 5g of water, stir for 30 minutes, then add 12g of butyl titanate and 3g of surfactant P123, continue stirring for 30 minutes, seal, and statically treat at 120°C for 12 hours. The obtained product is filtered, washed, dried, and calcined at 550°C for 14 hours to obtain iodine niobium oxide HNbO (IO 3 ) 4 and titanium dioxide TiO 2 A mixture of NbTi and NbTi-1.
[0042] Taking NbTi as the proton conductor, the conductivity at 120°C and 10RH% is 0.129S / cm; at 280°C and 5RH%, the conductivity is 0.173S / cm.
[0043] Example 3
[0044] 1) Mix niobium pentoxide (0.6 mmol) and hydrofluoric acid (40% by mass, 4 ml), heat to 140°C and stir until dissolved, add ammonia water to adjust the pH to 6; add 10 ml of 1 mol / L iodic acid aqueous solution, seal, and statically treat at 160°C for 72 hours. The obtained product is filtered, washed, dried, calcined at 550°C for 6 hours, and ground into a uniform powder to obtain iodinated niobium HNbO(IO 3 ) 4 ;
[0045] 2) 1g niobium iodate HNbO(IO 3 ) 4 Add 5g of water, stir for 30 minutes, then add 5g of ethyl orthosilicate, 5g of ethyl zirconate and 3g of surfactant F127, continue stirring for 30 minutes, seal, and statically treat at 140°C for 6 hours. The obtained product is filtered, washed, dried, and calcined at 400°C for 6 hours to obtain iodine niobium oxide HNbO (IO 3 ) 4 With silicon dioxide SiO 2 and zirconium dioxide ZrO 2 mixture of
[0046] 3) Phosphoric acid and boric acid (molar ratio 2:1) were mixed, heated to 280°C and stirred continuously to obtain a white slurry precursor. The obtained precursor was calcined at 350°C in a muffle furnace for 20 hours, and the obtained material was ground into a uniform powder, namely BPO. 4 powder;
[0047] 4) 0.1 g of BPO prepared in step 3)4 The powder was added to 1 g of water, mixed with 1.0 g of the mixture prepared in step 2) by ball milling for 8 hours, and dried to obtain a proton conductor, which was designated as NbBPSiZr-1.
[0048] Taking NbBPSiZr-1 as the proton conductor, the conductivity at 120°C and 10RH% is 0.167S / cm; at 280°C and 5RH%, the conductivity is 0.184S / cm.
[0049] Example 4
[0050] 1) Mix niobium pentoxide (0.6 mmol) and hydrofluoric acid (40% by mass, 4 ml), heat to 120°C and stir until dissolved, add ammonia water to adjust the pH to 6; add 10 ml of 1 mol / L iodic acid aqueous solution, seal, and statically treat at 180°C for 72 hours. The obtained product is filtered, washed, dried, calcined at 500°C for 12 hours, and ground into a uniform powder to obtain iodinated niobium HNbO(IO 3 ) 4 ;
[0051] 2) 1g niobium iodate HNbO(IO 3 ) 4 Add 5g of water and stir for 30 minutes, then add 15g of tetraethoxysilane and 3g of surfactant CTAB, continue stirring for 30 minutes, seal, and statically treat at 80°C for 18 hours. The obtained product is filtered, washed, dried, and calcined at 600°C for 6 hours to obtain iodinated niobium HNbO (IO 3 ) 4 and silicon dioxide SiO 2 mixture of
[0052] 3) Phosphoric acid and boric acid (molar ratio 2:1) were mixed, heated to 260°C and stirred continuously to obtain a white slurry precursor. The obtained precursor was calcined at 350°C in a muffle furnace for 20 hours, and the obtained material was ground into a uniform powder, namely BPO. 4 powder;
[0053] 4) 0.04 g of BPO prepared in step 3) 4 The powder was added to 1 g of water, mixed with 1.0 g of the mixture prepared in step 2) by ball milling for 8 hours, and dried to obtain a proton conductor, which was designated as NbBPSi-2.
[0054] Taking NbBPSi-2 as the proton conductor, the conductivity at 120°C and 10RH% is 0.137S / cm; at 280°C and 5RH%, the conductivity is 0.175S / cm.
[0055] Example 5
[0056] 1) Mix niobium pentoxide (0.6 mmol) and hydrofluoric acid (40% by mass, 4 ml), heat to 120°C and stir until dissolved, add ammonia water to adjust the pH to 6; add 10 ml of 1 mol / L iodic acid aqueous solution, seal, and statically treat at 180°C for 60 hours. The obtained product is filtered, washed, dried, calcined at 500°C for 12 hours, and ground into a uniform powder to obtain iodinated niobium HNbO(IO 3 ) 4 ;
[0057] 2) 1g niobium iodate HNbO(IO 3 ) 4 Add 5g of water, stir for 30 minutes, then add 15g of ethyl zirconate and 3g of surfactant F127, continue stirring for 30 minutes, seal, and statically treat at 120°C for 12 hours. The obtained product is filtered, washed, dried, and calcined at 500°C for 12 hours to obtain iodine niobium oxide HNbO (IO 3 ) 4 and zirconium dioxide ZrO 2 mixture of
[0058] 3) Phosphoric acid and boric acid (molar ratio 2:1) were mixed, heated to 260°C and stirred continuously to obtain a white slurry precursor. The obtained precursor was calcined at 350°C in a muffle furnace for 20 hours, and the obtained material was ground into a uniform powder, namely BPO. 4 powder;
[0059] 4) 0.1 g of BPO prepared in step 3) 4 The powder was added to 1 g of water, mixed with 1.0 g of the mixture prepared in step 2) by ball milling for 8 hours, and dried to obtain a proton conductor, which was designated as NbBPZr-1.
[0060] Preparation of a composite proton exchange membrane in which NbBPZr-1 is doped into polybenzimidazole as a proton exchange membrane additive: NbBPZr-1 is mixed with a polybenzimidazole solution (mass fraction 2.5%), the mass ratio of NbBPZr-1 to polybenzimidazole is 1:20, the resulting mixture is ultrasonically treated for 3 hours to obtain a membrane-forming solution, the membrane-forming solution is placed on a glass plate, and kept in an oven at 60°C for 12 to 60 hours to obtain a membrane material, and the obtained membrane material is immersed in phosphoric acid for 3 days to obtain PA-NbBPZr-1-PBI.
[0061] At 120°C, the conductivity at 5RH% is 0.177S / cm; at 180°C, the conductivity at 5RH% is 0.194S / cm.
[0062] Comparative Example 3
[0063] A polybenzimidazole solution (mass fraction 2.5%) was used as a membrane-forming solution, placed on a glass plate, and kept in an oven at 60° C. for 12 to 60 hours to obtain a membrane material. The obtained membrane material was immersed in phosphoric acid for 3 days to obtain PA-PBI.
[0064] At 120°C, the conductivity at 5RH% is 0.135S / cm; at 180°C, the conductivity at 5RH% is 0.157S / cm.
[0065] Compared with Example 2, in Comparative Example 1, except for the inorganic oxide TiO 2 The other compositions and parameters are the same except that the comparative example 2 does not contain boron phosphate BPO. 4 By comparing Example 2 with Comparative Examples 1 and 2, it can be seen that the inorganic oxide and boron phosphate in the proton conductor of the present invention play an important role in improving the conductivity of the proton conductor. The nano-scale inorganic oxide can provide a rich surface area, act as a carrier and a skeleton, and react with iodinated niobium HNbO (IO 3 ) 4 It has strong interactions, can enrich the hydrogen bond network and promote proton conduction. In addition, BPO 4 The introduction of further improves the proton conductivity of the composite material. Therefore, in the present invention, iodine niobium oxide HNbO (IO 3 ) 4 , Boron Phosphate BPO 4 And inorganic oxide MO 2 The three work together to improve the conductivity of the proton conductor. Compared with Example 5, except that NbBPZr-1 is not included in Comparative Example 3, other compositions and parameters are the same. By comparing Example 5 with Comparative Example 3, it can be seen that the proton conductor in the present invention, as a proton exchange membrane additive, plays an important role in improving the conductivity of the PA-PBI membrane.
[0066] The above are only some embodiments of the invention, and do not limit the present invention in any form. All raw material ratios, upper and lower limits of working conditions and interval values in the preparation process of the present invention can realize the present invention, and the embodiments are not listed one by one here. Any person familiar with this profession, without departing from the technical solution of the present invention, when using the above technical content to make some changes or modifications to an equivalent embodiment of decorating, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the content of the technical solution of the present invention, still belongs to the scope of the technical solution of the present invention.
Claims
1. A proton conductor, characterized in that: The proton conductor consists of niobium iodate (HNbO(IO3)4), boron phosphate (BPO4) and inorganic oxide (MO2).
2. A proton conductor according to claim 1, characterized in that: The inorganic oxide MO2 is one or two of SiO2, TiO2 or ZrO2, and the crystal size of the inorganic oxide MO2 is 100-500nm.
3. A proton conductor according to claim 1, characterized in that: The mass ratio of the iodinated niobium oxide HNbO(IO3)4 to the inorganic oxide MO2 is 1:(2-15).
4. A proton conductor according to claim 1, characterized in that: The mass ratio of the boron phosphate BPO4 to the sum of niobium iodate HNbO(IO3)4 and the inorganic oxide MO2 is 1:(2.5-25).
5. The method for preparing a proton conductor according to claim 1, characterized in that: The steps include: (1) mixing niobium pentoxide and hydrofluoric acid, heating to 100-140° C. to dissolve, adding ammonia water to adjust the pH to 5-7, adding iodic acid, sealing, and statically treating at 150-180° C. for 48-72 hours; filtering, washing, drying, and calcining at 400-600° C. for 4-12 hours to obtain iodinated niobium HNbO(IO3)4; (2) mixing iodoniobium oxychloride HNbO(IO3)4, an inorganic oxide precursor and a surfactant, stirring for 30 to 60 minutes, sealing, and statically treating at 80 to 140° C. for 6 to 18 hours; filtering, washing, drying, and calcining at 400 to 600° C. for 6 to 18 hours to obtain a mixture of iodoniobium oxychloride HNbO(IO3)4 and an inorganic oxide MO2; (3) mixing phosphoric acid and boric acid solutions, heating to 220-280° C., to obtain a boron phosphate precursor; calcining the boron phosphate precursor at high temperature to obtain BPO4; (4) The BPO4 prepared in step (3) and the mixture prepared in step (2) are mixed by ball milling and dried to obtain the proton conductor.
6. The preparation method according to claim 5, characterized in that: The inorganic oxide precursor includes one or two of tetraethyl orthosilicate, ethyl titanate, butyl titanate, tetraethoxysilane, and ethyl zirconate, the surfactant includes one of F127, P123, and CTAB, and the mass ratio of the inorganic oxide precursor to the surfactant is (5-15):
3.
7. The preparation method according to claim 5, characterized in that: The temperature of high-temperature calcination of the boron phosphate precursor is 300-600° C., and the time is 2-24 hours.
8. Use of the proton conductor according to any one of claims 1 to 4 or the proton conductor prepared by the preparation method according to any one of claims 5 to 7, characterized in that: The proton conductor is used as a proton exchange membrane additive or a fuel cell membrane electrode proton conductive material, and has an applicable temperature of 100 to 300°C.
Citation Information
Patent Citations
Inorganic-organic hybrid membrane for ionic interchange, preparation thereof and use in electrochemical devices
ES2310484A1